TAP. Theatre and Auditorium, Poitiers. France. - Sequeira, Marta (TC Cuadernos, 2022)
The Theatre and Auditorium of Poitiers is located at the edge of the historic city centre, on a steep slope that descends vertiginously towards the railway line and the high-speed train station. In the continuity of the urban fabric, the complex appears as a limestone acropolis – constituting a public terrace with a visual dominance over the landscape of the Boivre river valley – on which stand, suspended, the crystalline-looking parallelepiped volumes of an auditorium and a theatre. While the auditorium, with around 1,000 seats, supports a very specific programme, the theatre, with around 700 seats, supports an informal, multipurpose programme. The auditorium consists of a parallelepiped room with a fl at audience – avoiding primary and fragmented absorption – and with a width of less than 21 metres – highlighting the lateral reflections. The wooden covering of the side walls is a quadratic diffusion system, redistributing the sound in a homogeneous way, so that all spectators receive the music simultaneously and without energy loss. The floor and the stage, also made of wood, do not contain a single metal part. Apart from the audience, it is possible to watch the concert from a row of chairs in the galleries, or from three rows that, placed behind the stage, allow a reverse listening.